KAJIAN HUKUM TENTANG PEMBATALAN HASIL LELANG EKSEKUSI OBJEK JAMINAN HAK TANGGUNGAN OLEH PENGADILAN KARENA TIDAK BERWENANGNYA DEBITUR PEMBERI HAK TANGGUNGAN (STUDI PUTUSAN No. 18/Pdt.G/2010/PN. TTD) - DINDA AYU PERMATASARI (PREMISE LAW JURNAL, 2016)
In a banking credit contract, a Bank is usually more interested in mortgage given by a debtor that can bound with collateral. The collateral has to legally belong to the debtor according to the prevailing legal provisions. The research used judicial normative and descriptive analytic. The result of the research shows that the hypothecation is implemented when a debtor is default in paying off his debt so that creditor has the fight to sell the collateral in auction hall in order to get his right and give the remaining to the debtor. The legal ground of judge's consideration in revoking the foreclosure sale because the debtor has no right to give the collateral under the verdict. that the Bank as the creditor who holds Hypothecation certificate does not have any authority/privilege as stipulated in UUHT No. 4/1996 on the Collateral. Besides that, credit contract between creditor and debtor doe not have any collateral anymore although hypothecation contract has been signed Keywords: Revocation, Auction of Collateral, Court, No Authority of Debtor in Giving Collateral